Diversity of beetles (coleoptera) in mount Serambu, Bau, Sarawak - Sobiratul Addawiyah, binti Ismail. (Universiti Malaysia Sarawak (UNIMAS), 2013)
A total of 1602 individuals, representing 122 species consist of 65 subfamilies from 26 families of beetles were captured during this study at Mount Serambu, Bau, Sarawak within 22 days by using three methods which were beating, hand picking and Modified Pennsylvania light trap. Family Chrysomelidae represented the most diverse and common group at the sampling site with 25 species. The most abundant species was Ozomena sp. (F: Chrysomelidae). However, some groups of beetle are considered low in abundance because they are very low in number of individuals as well as species numbers. Most of them were encountered ITom the lower elevations. The overall Shannon Diversity Index was 2.276. Furthermore, there is a significant difference between species diversity of beetle in lower elevation and upper elevation at Mount Serambu when the Shannon Diversity index had been tested with Shannon Diversity Index t-test, tcalculalcd>tcrilical (5.046> 1.96). The species diversity index at lower elevation is H'= 3.4149 higher than at the upper elevation, H'--2.9541. The difference of species diversity between both elevations was influenced by vegetation types existed in that elevation.